2005
DOI: 10.1002/polb.20474
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of the δ‐form and mesophase of syndiotactic polystyrene membranes prepared from different organic solvents

Abstract: Syndiotactic polystyrene (sPS) membranes were prepared with different organic solvent systems and compared to get the information about the -form complexing behavior of sPS. Further, the guest molecules included in the clathrate form of sPS are removed by stepwise extraction method. The conformational changes during the TTGG helical formation of sPS/organic solvent systems have been identified by FTIR spectroscopy, and it was concluded that the TTGG helices were constructed in regular sequences, which depends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…20,21 The pore size has been reported to be 115 Å´3. 21 The sorption and desorption of organic solvents in the nanopores of d e -sPS were reported by Guerra and colleagues, 22,23 Tsujita and colleagues [24][25][26][27] and our group. 28,29 This porous structure is very attractive not only from an academic but also from a practical view, because it is applicable as a sensor for detecting small amounts of organic solvents, adsorption of chemical compounds and so on.…”
Section: Introductionmentioning
confidence: 56%
“…20,21 The pore size has been reported to be 115 Å´3. 21 The sorption and desorption of organic solvents in the nanopores of d e -sPS were reported by Guerra and colleagues, 22,23 Tsujita and colleagues [24][25][26][27] and our group. 28,29 This porous structure is very attractive not only from an academic but also from a practical view, because it is applicable as a sensor for detecting small amounts of organic solvents, adsorption of chemical compounds and so on.…”
Section: Introductionmentioning
confidence: 56%
“…Presently, polymeric nanoporous crystalline phases have been described for s‐PS and poly(2,6‐dimethyl‐1,4‐phenylene oxide) …”
Section: Introductionmentioning
confidence: 99%
“…In particular, for s‐PS, two nanoporous crystalline phases (δ and ε) have been discovered, which can absorb several guest molecules producing clathrate and intercalate co‐crystals. Films presenting s‐PS/active‐guest co‐crystals have been proposed as advanced materials for optical, magnetic, and ferroelectric applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[35,36] The absorption rate of solvent molecules was enhanced by a porous aerogel with a mesh structure, which was prepared by treating the sPS gel in scCO2. [37][38][39] The relationship between the size of the solvent molecule and the cavity volume of e-sPS was reported by Tsujita et al [40][41][42][43] It was shown that the cavity volume of -sPS is reduced after extracting the solvent molecules.…”
Section: Introductionmentioning
confidence: 99%